Implementation of Extension Journalism in Cyber Media as a Communication Channel for Sustainable Development - Metha Madonna; Fikri Reza (Pascasarjana, Mataram University, 2023)
Use Ideally the national press supports the government through counselling-oriented journalism as a form of development communication. The concept of counselling journalism reflects the success of the